optimisation des paramétres du foctionnement de la colonne dépropaniseuer - بالقاسم, سعدان; مسعود, بكاكرة (University of El-Oued, 2020)
"Liquefied petroleum gas is a mixture of gaseous hydrocarbons, consisting mainly of 80% of butane and 20% of propane under normal temperature and pressure conditions. Global LPG consumption is continuously growing due to its reliable economic record as a clean and efficient fuel for the future. The production of the latter must meet well-defined standards and specifications. For, we carried out a study to improve the operating parameters of the depropanizer column. And To ensure proper fractionation of this column, the feed to column C703 must have a temperature of 70 ° C and a pressure of 16.25 atm.abs. Therefore, the head temperature of the column will be 44 ° C and a pressure of 16 atm.abs and that of the bottom will be 97.7 ° C and a pressure of 16.5 atm.abs " "غاز البترول المسال عبارة عن خليط من الهيدروكربونات الغازية يتكون أساسًا من 80٪ من البيوتان و 20٪ من البروبان تحت ظروف الضغط والحرارة العادية. يتزايد الاستهلاك العالمي لغاز البترول المسال باستمرار بسبب سجله الاقتصادي الموثوق به باعتباره وقود نظيف وفعال للمستقبل. يجب أن يكون إنتاج الأخير محددًا جيدًا المعايير والمواصفات. لذلك ، أجرينا دراسة لتحسين معايير التشغيل لجهاز إزالة البروبان عمودي. ولضمان تجزئة هذا العمود بشكل صحيح ، يجب أن تحتوي التغذية في العمود C703 درجة حرارة 70 درجة مئوية وضغط 16.25 ضغط جوي. لذلك ، ستكون درجة حرارة رأس العمود 44 درجة مئوية وضغط 16 سيكون ضغط أجهزة الصراف الآلي والقاع السفلي 97.7 درجة مئوية وضغط 16.5 أجهزة الصراف الآلي "
Génie Pétrochimie مذكرة ماستر تخصص
Keywords: Gaz naturel, LPG, Optimization, depropanizer, condensate; الغاز الطبيعي ، غاز البترول المسال ، التحسين ، مزيل البروبان ، المكثفات